PENGARUH INFLUENCER DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK PASMINA DI INDONESIA - Savitri, Dien; Fikriyah, Khusnul (Jurnal Ekonomika dan Bisnis Islam, 2024)
The development of fashion trends, the desire to make purchases has increased even for items that are not truly needed. The purpose of this research is to identify and analyze the effect of influencers and price on the purchasing decisions of pashmina products in Indonesia. The quantitative method is used in this research, with primary data sources obtained through the distribution of online questionnaires. This study uses purposive sampling technique with a total of 106 respondents. The analysis in this study uses SEM-PLS analysis technique aided by Smartpls 4.0 software. From the testing and analysis conducted, this study finds that influencers and price have a significant influence on consumer purchasing decisions for pashmina products in Indonesia. The implication of the results of this research is that companies that use influencer services can provide quality content with their own characteristics to be able to have a positive impact on pashmina sales. Apart from that, affordable prices must be maintained in order to attract consumer interest.